Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.4067/s0717-95022020000300731
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sex-Related Differences in Body Composition to Change of Direction Speed in Police Officers While Carrying Load

Abstract: Regardless of sex or body size, police tasks may require officers to change direction speed (CODS) under occupational loads. The purpose of this study was to investigate body composition and CODS in female and male police cadets in both unloaded and occupationally loaded conditions. Body composition and CODS of 51 female (FPC) and 70 male police cadets (MPC) were assessed. Six body composition indices were used: Body mass index (BMI), percent body fat (PBF), percent of skeletal muscle mass (PSMM), protein fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 21 publications
0
23
1
Order By: Relevance
“…According to BMI ≥ 30 kg/m 2 , 22% of officers were classified as obese, while according to PBF > 25%, 49% were obese. This was about 3% higher difference than the results obtained for the 30-39 years group and about 8% higher than that of the Kukić, F. et al (2020). Accuracy and predictive capability of body mass index in evaluation of obesity and body fatness level in police officers combined sample of the current study.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…According to BMI ≥ 30 kg/m 2 , 22% of officers were classified as obese, while according to PBF > 25%, 49% were obese. This was about 3% higher difference than the results obtained for the 30-39 years group and about 8% higher than that of the Kukić, F. et al (2020). Accuracy and predictive capability of body mass index in evaluation of obesity and body fatness level in police officers combined sample of the current study.…”
Section: Discussioncontrasting
confidence: 68%
“…Obesity represents one of the leading public health problems in the world (WHO, 2017), which has been associated with coronary heart disease, hypertension, diabetes mellitus, lower quality of life and sleeping problems (Violanti et al, 2006;Charles et al, 2008;Alghamdi et al, 2017). Moreover, increased body fatness has been negatively associated with physical performance (Dawes et al, 2016), and is a significant predictor of health-related and occupational performance-related physical fitness outcomes (Kukic et al, 2018;Kukić et al, 2020). Considering this, police agencies have been working on development of assessments, treatments and prevention policies to address the negative changes in obesity related to work that is more sedentary and life habits of police officers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems that males are more prone to changes in ratio of fat and muscle tissue, mostly on account of body fat increase, while females, although more prone to loss of SMM, are affected by both. These variations are often reflected in physical performance when fat mass (ballast mass) increases over the criterion level, thus lowering PP and PSMM, when it becomes heavy enough to hinder the outcomes of muscle contractions, resulting in lower performance [ 3 , 20 ]. Given that the metabolism slows down by age, and an increase in body fatness is likely to occur, a good PP in adulthood, and its maintenance throughout aging could have a preventive effect on health and performance (hence quality of life), which could be obtained by regular physical activity and good eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the diversity of police jobs, the permanent follow-up of physical fitness and general health may be a good component of the strategy to keep the officers healthy (Anderson et al, 2001;Cvorovic and Maamari, 2017;Vukovi c et al, 2020). Many studies have shown that effectiveness in police jobs requires general and specific physical abilities and skills (Kukic et al, 2018;Kuki c et al, 2020;Dawes et al, 2017;Orr et al, 2017). In this regard, long sitting hours together with increased stress level have been reported to increase the risk of metabolic syndrome and cardiovascular disease (CVD) (Garbarino and Magnavita, 2015;Violanti et al, 2006Violanti et al, , 2009.…”
Section: Discussionmentioning
confidence: 99%